2007
DOI: 10.1007/s00702-007-0811-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential behavioral syndrome evoked in the rats after multiple doses of SSRI fluoxetine with selective MAO inhibitors rasagiline or selegiline

Abstract: This study investigated whether rasagiline and selegiline (MAO-B inhibitors) induce serotonin syndrome in fluoxetine-treated rats. Rats received rasagiline (0.1, 0.5, 2.0 mg/kg), or selegiline (0.8, 4.0, 16.0 mg/kg) (doses reflecting the clinical ratio of 1:8 base) in drinking water for 28 days. During the last 21 days, they received injections of fluoxetine 10 mg/kg (controls received water only, then saline injections; a fluoxetine only group received water only then fluoxetine). Serotonin syndrome was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
4
2
Order By: Relevance
“…By comparison, L-DOPA efficacy was observed on the first day of testing in L-DOPA-naïve rats regardless of SSRI dose and this was maintained over 3 weeks. Though adverse side effects have been reported in PD patients and rodent models treated with SSRIs no such observations were made in the present study (Linazasoro 2000; Speiser et al, 2008). From a translational point of view, that recurrently administered SSRIs not only reduced LID, but also maintained L-DOPA’s anti-parkinsonian efficacy is an attractive feature of this strategy.…”
Section: Discussioncontrasting
confidence: 66%
“…By comparison, L-DOPA efficacy was observed on the first day of testing in L-DOPA-naïve rats regardless of SSRI dose and this was maintained over 3 weeks. Though adverse side effects have been reported in PD patients and rodent models treated with SSRIs no such observations were made in the present study (Linazasoro 2000; Speiser et al, 2008). From a translational point of view, that recurrently administered SSRIs not only reduced LID, but also maintained L-DOPA’s anti-parkinsonian efficacy is an attractive feature of this strategy.…”
Section: Discussioncontrasting
confidence: 66%
“…Bairy et al concluded that prenatal fluoxetine administered to rats caused weight loss and a delay in the transient motor development of fetuses, although it did not, however, compromise postnatal behavior, thus supporting the findings of Speiser et al 21,29 Most studies demonstrate that fluoxetine-treated rats bear low weight offspring. Vartazarmian et al, however, found no weight alterations in fetuses of fluoxetine-treated rats.…”
Section: Discussionmentioning
confidence: 80%
“…Experimental studies in animal models and healthy human subjects have reported that the coadministration of rasagiline and serotonergic antidepressants does not induce STS . Several investigators have characterized and summarized the tolerability profile of concurrent rasagiline and antidepressants (R+ADT) in patients with PD .…”
Section: Diagnostic Criteria For Serotonin Toxicity Syndromementioning
confidence: 99%